Analisis Literatur Tentang Peran Database Management System dalam Efektivitas Aplikasi Pembelajaran Digital di Perguruan Tinggi - Dea Miranti Hajiriah Manurung; Muhammad Irwan Padli Nasution (Jurnal Motivasi Pendidikan dan Bahasa, 2026)
This research is a literature analysis study aimed at identifying and synthesizing the role of Database Management Ststems (DBMS) in supporting the effectiveness of digital learning applications in higher education environments. The study sources include ten scientific articles published between 2011 and 2025, convering the topics of Academic Information Systems (SIAKAD), Learning Management Systems (LMS), digital based education administration, e- learning development, and database system optimization. The method used is a literature review with a content analysis approach and thematic synthesis of findings from various previous studies. The study result indicate that DBMS plays a central and multidimensional role in the digital education ecosystem, encompassing three main dimensions: (1) a technical function as an infrastructure for efficient data storage, management, and retrieval using DDL, DML, and DCL languages; (2) an administrative function in centrally and real- timely integrating attendance, assessment, academic reporting, and learning administration processes; and (3) a strategic function in supporting data drivendecision- making and encouraging student learning independence through the LMS. This study also identified ongoing implementations challenges, including limited technological infrastructure, low human resource competency in managing digital systems, and data security and integrity issues. The most commonly used DBMS in higher education contexts include MySQL, PosttgreSQL, MongoDB, Oracle, and SQLite. These findings confirm that DBMS optimization is not merely a technical necessity, but rather a strategic component of the sustainable digital transformations of higher education.